New knowledge and operative framework of urban health - Serra, Federico; Capolongo, Stefano; Cosimi, Alessandro; Crialesi, Roberta; Corsaro, Lucio; da Empoli, Stefano; Dotta, Francesco; Gaudosio, Antonio; Gianfrilli, Daniele; Grasso, Luciano; Lenzi, Francesca Romana; Mazzoni, Eleonora; et al. (Acta Biomedica Atenei Parmensis, 2024)
It is easy to understand how healthy choices bring us to an healthy life. The capability of adopt healthy lifestyles is due by opportunities, possibilities and personal motivation, all variabilities influenced by external factors. Some citizens, unlike others, have easy access to affordable, fresh and healthy foods. Some citizens, similar to others, have easy access to safe places where to walk, run, ride bicycles and play. This also shows that when some vulnerable groups get sick, the impact is wider, and the consequences are worse. The issue of the social-health inequality has gained global relevance after the Covid-19 pandemic. The Coronavirus has damaged different populations that were already fighting predictable diseases such as obesity, diabetes, cardiovascular pathologies, and cancers. This has underlined the need to establish collaboration throughout the different sectors in order to reduce the spread of predictable diseases. The solutions are known. If we offer the right incentives, we can modify the social and economic environments that affect the risk factor in order to gradually solve the gap regarding health inequalities. Cities have an important responsibility regarding this, other than the possibility of taking a lead role in promoting innovative solutions that create healthy and sustainable spaces and communities to support citizens in adopting healthy choices. But specialists, who can develop multi-sectorial plans and deal with the different aspects that operate in a city's social health system, are needed. In this context, new professional competencies like Health City Managers (HCM), who are able to elaborate on Urban Health Framework (UHF), appear necessary to facilitate the collaboration between public health entities to grant the creation of healthy environments. The HCM approach analyses the different factors that affect environment, where public and private sectors can operate in a functional way.